Comparisons of Guidelines and Recommendations on Managing Antineutrophil Cytoplasmic Antibody-Associated Vasculitis. - Little, Mark; Geetha, Duvuru; Jin, Quiyu; Scott, Jennifer; Hruskova, Zdenka; Hanouneh, Mohamad; Tesar, Vladimir; Seo, Philip; Jayne, David; Pagnoux, Christian (My University, 2018)
Antineutrophil cytoplasmic antibodies−associated vasculitis (AAV) is associated with high morbidity or mortality, especially if not promptly diagnosed and treated. Many inroads have been made in the understanding of the pathophysiology that leads to exploration of novel therapies. Randomized controlled trials over the last 2 decades have better delineated and expanded therapeutic options and set the stage for an evidence-based approach. Since 2014, 4 scientific societies have systematically reviewed the existing data and have formulated evidence-based recommendations for the management of AAV. These recommendations cover diagnosis, remission induction and maintenance treatment, and prevention of long-term complications. This review is a comparative analysis of the recently published recommendations of the European League Against Rheumatism/European Renal Association-European Dialysis and Transplant Association, the British Society of Rheumatology, the Canadian Vasculitis Research Network, and the Brazilian Society of Rheumatology, and aims to determine common ground among them and highlights the differences among the recommendations.
PUBLISHED
Keywords: ANCA-associated vasculitis; Treatment guidelines; Immunology, Inflammation & Infection